Engineered PES/SPES nanochannel membrane for salinity gradient power generation. (May 2019) - Huang, Xiaodong; Zhang, Zhen; Kong, Xiang-Yu; Sun, Yue; Zhu, Congcong; Liu, Pei; Pang, Jinhui; Jiang, Lei; Wen, Liping
Abstract: Nature is the source of human being's creativity and always inspires people to break through the existing bottleneck of science and technology. Electric eel (Electrophorus electricus) relying on ion channel in electrocyte can convert salinity gradient energy to electricity power with potentials of 600 V to stun prey and ward off predators. Inspired by biological ion channels, artificial nanochannels have been extensively explored to mimic the control of ion flow in nanosize confinement space and apply in salinity gradient power generation. In this paper, polyether sulfone/sulfonated polyether sulfone (PES/SPES) membranes with large amount of nanochannels are constructed by using phase separation method to be applied in the salinity gradient power generation field. The content of SPES, the concentration of casting solution, and the thickness of prefabricated membrane were taken into account to control the structural and surface charge distribution of membrane. The prepared serials PES/SPES membrane with nanopore structure display much proper cation selectivity, excellent ion conductivity and output power density (reach up to 2.48 W/m 2 ) for salinity gradient power generation. In addition, the proposed membrane with low cost and easy casting process shows great potential for the practical application in salinity gradient power generation. Graphical abstract: Engineered PES/SPES membrane with nanochannel structure displays excellent ion conductivity property and output power density for salinity gradient power generation.fx1 Highlights: PES/SPES membrane with nanochannel and ultrathin functional layer is constructed by phase separation method. The PES/SPES membrane shows excellent ion transport and high output power density for salinity gradient power generation. The low cost and easy fabrication of the PES/SPES membrane make a potential for large-scale application.